Public administration as an autonomous system. Right to public service - Vázquez Pérez, Eduardo Daniel (2022)
Talking about the right to public service in Mexico is a huge challenge, since the system in which the country’s institutions have been built is extremely corrupted due to the interests of the political parties that hold power. Even though there are some regulatory instruments that allow the proper functioning of public administration, they have been overtaken by other interests. This shows that legislative proceedings hardly consult the needs of society so that society can be favored by the programs and services provided by the State to citizens but fulfill positive legal aspects that are not compatible with the social reality in the country.